Legal Interpretation of the Position of the Papuan People's Assembly in the Expansion of Provinces within the New Autonomous Region of Papua - Decky DA Wospakrik (Journal of Law, Politic and Humanities, 2025)
The purpose of this study is to analyze changes in the legislation on Papua's special autonomy with the aim of expanding the province of Papua. The purpose of expansion is carried out by first making changes to the legislation related to Papua's special autonomy with fast track legislation). This study uses a normative method, which traces the legislation related to interpreting the changes in the regulations. The results of the study on changes to the Law by means of fast track legislation (FTL), provide an interpretation that the expansion of the province of Papua can be carried out by changing Article 76 in the Special Autonomy Law before the change by placing the word "can" which is the interpretation that the formation of a new province in Papua can be done without going through the approval of the MRP as required by the Special Autonomy Law before the change. Based on the findings, the Amendment to the Special Autonomy Law provides space for FTL, the central government and the DPR to be carried out top-down in the expansion of the province in Papua without the involvement of the MRP. The central government and the DPR view Papua in a political context to reduce the political turmoil that occurs in Papua by viewing the expansion as a solution to improve the welfare of indigenous Papuans without looking at the social and cultural impacts on indigenous Papuans who are represented in the MRP Institution.